Identifying and prioritizing factors affecting the quality of internal controls - Asharyon Ghomizadeh, Mehdi; Khan Mohammadi, Mohammad Hamed; Mahmoudi, Mohammad (Management Strategies and Engineering Sciences, 2024)
The aim of this research is to identify and prioritize factors affecting the quality of internal controls. To achieve this objective, a set of indicators and components related to the quality of internal controls were identified through a review of theoretical foundations and previous studies, as well as interviews with experts and professionals in the field. A qualitative research approach using a multiple-grounded theory method was applied. Therefore, data analysis was conducted at both the empirical and theoretical levels. The required empirical data was obtained through theoretical sampling of 15 semi-structured interviews with professionals who had successful experience in implementing the mentioned system during the years 2019 and 2023. The theoretical data was obtained through a literature review. The results of the qualitative research revealed several conditions and factors that influence the quality of internal controls. Causal conditions include the structure of the board, characteristics of internal auditors, and board committees. Core conditions refer to environmental factors and performance factors. Strategies, such as proper documentation of procedures, external auditing, and organizational components, emerged as key actions and interactions in improving internal control quality. Contextual factors include ownership structure, company structure, and managerial decisions. Intervening factors were identified as economic, political, regulatory, and market factors, as well as the role of legislators. The outcomes of the study highlight the impact of internal controls on asset protection, the efficiency of internal controls in reducing risks and penalties, the effect of internal controls on organizational productivity, customer satisfaction, and the overall quality of both financial and non-financial information.